2010
DOI: 10.1159/000314699
|View full text |Cite
|
Sign up to set email alerts
|

Octenidine Dihydrochloride, a Modern Antiseptic for Skin, Mucous Membranes and Wounds

Abstract: Octenidine dihydrochloride (octenidine) was introduced for skin, mucous membrane and wound antisepsis more than 20 years ago. Until now, a wealth of knowledge has been gained, including in vitro and animal studies on efficacy, tolerance, safety and clinical experience both from case reports and prospective controlled trials. Nowadays, octenidine is an established antiseptic in a large field of applications and represents an alternative to older substances such as chlorhexidine, polyvidone-iodine or triclosan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0
20

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(167 citation statements)
references
References 130 publications
5
142
0
20
Order By: Relevance
“…The results obtained in this study encourage considering OCT, which is well tolerated and without resistances reported so far [18], as an alternative antiseptic for controlling the spread of MR bacteria, either being Gram-positive or Gramnegative. Further studies are required to better evaluate the impact of OCT in clinical practice for preventing infections caused by MRGN, such as that recently performed by Gastmeier et al [19], who showed no significant impact on the prevention of MRGN acquisition in intensive care units.…”
Section: Discussionsupporting
confidence: 63%
“…The results obtained in this study encourage considering OCT, which is well tolerated and without resistances reported so far [18], as an alternative antiseptic for controlling the spread of MR bacteria, either being Gram-positive or Gramnegative. Further studies are required to better evaluate the impact of OCT in clinical practice for preventing infections caused by MRGN, such as that recently performed by Gastmeier et al [19], who showed no significant impact on the prevention of MRGN acquisition in intensive care units.…”
Section: Discussionsupporting
confidence: 63%
“…33,34 OCT is commonly used at a concentration of 0.1%-0.2% and PHMB is used at 0.2% as an antiseptic. 25,35,36 It was demonstrated that all antiseptic solutions had both bacteriostatic and bactericidal effects against the test microorganisms, as CHX was used at 150 mg/L and OCT and PHMB were used at 120 mg/L in the present study. All of the bacterial groups that were chosen as the test microorganisms in this study were the most common cariogenic bacteria isolated from caries lesions.…”
Section: Discussionmentioning
confidence: 66%
“…Octenidine dihydrochloride is a cationic lipophilic biocide of high molecular weight ( Fig. 1; Table 1) and is an efficient antiseptic for skin, mucous membranes, and wounds (15). The efficacy of the bispyridine derivative octenidine was reduced 2-fold by deletion of the main M. smegmatis porin MspA, but not by further deletions of mspC and mspD (Table 1; Fig.…”
Section: Resultsmentioning
confidence: 99%